The Relationship Between Peer Social Support and Academic Stress Among Students - Yunidar, Yunidar; Nirwana, Herman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe: (1) the level of academic stress among students, (2) the level of peer social support, and (3) to test the significance of the relationship between peer social support and academic stress experienced by students. This research employs a quantitative method with a descriptive correlational research design. The population of this study consists of 421 students from SMPN 1 Kotanopan who were registered during the July-December semester of the 2025 academic year, with a sample of 241 students selected using Stratified Random Sampling. The instruments used were the